Analisis Pantun Daerah Senjang Kota Lubuklinggau yang Mengandung Pendidikan Karakter Religius dan Gotong Royong - Tarmizi; Abdul Muktadir; Puspa Djuwita (UNIB Press, 2024)
This study aims to describe the value of religious character education and mutual cooperation in the poetry of the sejang area of ​​Lubuklinggau City. The benefit of the research aims to find out the meaning and significance of the rhyme in the area of ​​the sejang area of ​​Lubuklinggau city. This research is a type of qualitative descriptive research, with content analysis method. The procedure for this research is to study the literature, namely reading and taking notes to find out the form of research data in the form of values ​​of religious character education and mutual cooperation in rhymes in the sejang area of ​​Lubuklinggau city. The techniques used in data collection in this study were library techniques, notes, and coding and documentation. The results of this study indicate that there are values ​​of religious character education and mutual cooperation in the rhymes of the sejang area of ​​Lubuklinggau city.